Calprotectin as a biomarker of inflammation - Kozar, Valentyna; Shapovalova, Olha; Butko, Yaroslava; Khaleeva, Olena (Annals of Mechnikov's Institute, 2025)
Despite the fact that Calprotectin (S100A8/A9) has long been recognized as a sensitive marker for inflammatory bowel diseases, current data broaden the understanding of its use as a sensitive indicator in other inflammatory conditions, including systemic ones. The article analyzes data related to the modern perspective on the use of Calprotectin as an effective marker of inflammation. Fecal Calprotectin is considered an important marker of inflammatory bowel diseases and it is currently used in the differential diagnosis of inflammatory and functional bowel disorders. Serum Calprotectin is regarded as a promising laboratory marker with significant clinical relevance in conditions such as rheumatoid arthritis, hypertension in pregnant women, mild and severe preeclampsia, ileitis, inflammatory kidney diseases, allergic airway inflammations, sepsis, and others. Recent studies have demonstrated that the sensitivity and specificity of serum Calprotectin are comparable to those of well-known acute-phase indicators such as Calprotectin and C-reactive protein, and in certain cases, such as neonatal sepsis, it may even be more promising. Calprotectin has emerged as a highly sensitive biomarker of inflammation across a wide spectrum of pathological conditions. Fecal Calprotectin, in particular, is widely recognized as a validated, non-invasive biomarker for the detection and monitoring of intestinal inflammation. Advances in understanding the activation pathways of various cell types under physiological and pathological conditions have shed light on the involvement of Calprotectin in inflammatory response mechanisms. This has led to increased interest in quantifying S100A8/A9 levels in diverse biological fluids. Recent studies have demonstrated the prognostic value of serum Calprotectin in autoimmune diseases, malignancies, pulmonary disorders, sepsis, and other inflammatory states. The assessment of calprotectin concentrations in urine, synovial fluid, bronchoalveolar lavage, and sputum provides clinically relevant information regarding the severity of inflammation and disease progression. Research findings confirm the importance of Calprotectin as an inflammation biomarker in diseases where neutrophils play a key role in pathogenesis, since the neutrophil protein S100A8/A9 is one of the regulators of their activation.